Metafizičko pamćenje Vjačeslava Ivanova - Benčić, Živa (Array, 1998)
Vjačeslav Ivanov, Russian scholar of culture, uses the notion of memory mostly in two ways: on one hand it is for him the principle which insures the continuity and persistence of culture (cultural memory), on the other it is the source of artistic creation. In both its meanings the concept of memory, which Vjačeslav Ivanov bases upon the philosophical tradition of Plato and Plotinus, implies human consciousness in touch with the ideal and the absolute. It is, to use Plotinus's phrase, the return of the soul to the divine sources. The article also deals with a significant aspect of the concept of memory, crucial for Vjačeslav Ivanov as a poet. It refers to the autobiographical memory, which is not at all bereft of metaphysical connotations. Taking the autobiographical poem "Early childhood" ("Mladenčestvo") as an example, the author tries to show how Ivanov, by his choice and illumination of particular events of his childhood, enlivens on deeper, or rather, symbolical level of the work the general myth of the Paradise lost, of "the Edenic state" of the human race, and thus also transforms the memory of his own past into some kind of "return to his origin".